Interculturality in the English language classroom: ways to promote critical language education - Schulz, Mariana; Xypas, Rosiane (The ESPecialist, 2024)
In this article, we will reflect on the role of interculturality as a critical approach to teaching English, which aims to promote respect, equality, and social justice. Therefore, we join Decolonial Studies to the guidelines of postmethod, aiming to offer macro-strategies and attainable practices that favor learners' sensitization to other cultures and worldviews in a non-hierarchical way, questioning power relations and social inequalities. This is qualitative action research, which was undertaken in two stages: (1) bibliographical research and (2) the elaboration of a workshop/intervention. While still in progress, we hope that, on completion, the research will achieve the proposed objective, which is to contribute to critical initial teacher training.